OPTIMALISASI WAKTU DAN BIAYA PROYEK KONSTRUKSI DENGAN PENAMBAHAN JAM KERJA DAN TENAGA KERJA MENGGUNAKAN METODE TIME COST TRADE OFF - Raga, Andi Ahmad (Universitas Negeri Surabaya, 2023)
Many things can occur during the execution of a construction project that could increase the time required to complete it and delay it. Delays are caused by a variety of factors, including site-specific conditions, design changes, weather effects, unmet demand for workers, supplies, or equipment, errors in planning or specification, and involvement of the project owner or owner. The Northwest Citraland Shophouse Construction Project is planned to be completed in a period of 248 days with a budget plan cost of Rp 655,404,231.46. Acceleration is needed so that the construction of the project can be completed in accordance with the plan and the implementing contractor does not suffer losses due to project delays. The application of the Time Cost Trade Off method is expected to provide several alternative acceleration options so that the implementation of construction projects is efficient in terms of time and cost. The acceleration alternative in this study uses the acceleration of additional working hours and additional labor on the Northwest Citraland Surabaya Shophouse Construction Project. It aims to determine the comparison of time and cost generated after acceleration using these 2 alternatives. The analysis of time cost trade off results in Alternative 1 obtained an optimal duration of 223.6 days at a cost of Rp 650,010,588.07 with time and cost efficiency of 9.84% and 0.82%, in Alternative 2 obtained an optimal duration of 219. 3 days at a cost of Rp 650,130,175.97 with time and cost efficiency of 11.57% and 0.80%, and in alternative 3 obtained an optimum duration of 213.1 days at a cost of Rp 648,624,342.81 with time and cost efficiency of 14.06% and 1.03%.